Assessing the Role of CSR Practices of Commercial Banks in Enhancing Financial Inclusion: A Study on Banking Sector in Bangladesh - Haldar, P.K.; Rahman, S.M. Mahbubur; Mia, Md. Shahin; Ahmed, Ferdoushi; Bashawir, Ahmad (International Journal of Economics and Financial Issues, 2016)
Financial inclusion is currently a high priority policy goal for developing and developed countries in order to ensure stable and equitable economic growth. This study aims to assess the role of Corporate Social Responsibility (CSR) initiatives of commercial banks in enhancing financial inclusion in Bangladesh. The study also focuses on the benefits of financial inclusion and overall financial inclusion scenario of banking sector in the country. The study is based on secondary data extracted from the selected commercial banks for the period of 2008- 2012. The analyses show that geographic as well as demographic penetration of banking services in the country has increased significantly during the last five years. Consequently, financial inclusion in terms of total population has increased from 48.86 percent in 2008 to 63.46 percent in 2012. However, the overall financial inclusion through banking services has followed a modest pace. The study also found that the private commercial banks are contributing more in enhancing financial inclusion through CSR practices than state owned commercial banks and foreign commercial banks. The findings of the study might be valuable for the commercial banks to judge their performance in terms of CSR practices among the overall banking sector in the country. The study might also be useful for policymakers to promote more effective policies and guidelines to ensure an equitable financial inclusion for all the people including poor, underserved and underprivileged group of the society. Keywords: Corporate Social Responsibility (CSR), Commercial Bank, Financial Inclusion, Bangladesh JEL Classifications: G2, M14